Molecular Study of Eimeria species in Quail birds (Coturnix coturnix japonica) in Thi-Qar Province, Southern Iraq - Muntadher. M. Flayyih AL-Zarkoushi; Mohammed. Th. Salih AL-Zubaidi (Indian Journal of Forensic Medicine & Toxicology, 2022)
Fecal samples were collected from 330 quail birds from different areas of Thi-Qar province, Iraq. Allsamples were examined by traditional laboratory methods. Four species of Eimeria were diagnosed inquail (Eimeria bateri, Eimeria uzura, Eimeria tsunodai and Eimeria fluminensis), with a total infectionwas 64.54% (213 out of 330). DNA was extracted from 100 positive samples confirm the small subunitrRNA (18s) gene by Polymerase chain reaction using a general primer for Eimeria species, Sevengenotypes were according to the identify of DNA sequences of Eimeria species in Japanese quail, theaccession codes to NCBI-Genbank. using A comprehensive phylogenetic tree was generated in thepresent study, this details were being analyzed. This was the first molecular study in Iraq for Eimeriain common quail.